Is selective attention in anxiety characterised by biased attentional engagement with or disengagement from threat: Evidence from a colour naming paradigm - Clarke, Patrick; Hart, S.; MacLeod, C. (Textrum Ltd, 2014)
There has been considerable recent interest in identifying which specific processes characterize the widely observed anxiety-linked attentional preference for negative information. Two tasks, the emotional Stroop and the attentional probe, have been consistently employed to assess selective attention. However, until now, research designed to distinguished biased attentional engagement with, and disengagement from negative information has almost exclusively employed attentional probe task variants. To identify which of these attentional processes underpin the traditional emotional Stroop effect we developed a variant of the emotional Stroop capable of differentiating these two aspects of attentional selectivity. To assess biased attentional engagement with emotional word meanings, trials required participants to process the colour of a letter string before then measuring their speed to switch attention to its semantic content. To assess biased attentional disengagement from emotional word meanings, trials required participants to process the semantic content of a letter string before then measuring their speed to switch attention to process its colour. Our results indicate that the pattern of effects observed on the traditional emotional Stroop task are likely due to enhanced attentional engagement with the semantic content of negative stimuli, but not by impaired attentional disengagement from such negative semantic content.